Food Processing Technology Innovation to Improve Food Quality, Safety and Availability - Khamaludin Khamaludin (West Science Nature and Technology, 2023)
This research explores the role of food processing technology innovation in addressing critical challenges related to food quality, safety, and availability in West Java Province, Indonesia. The study employs a mixed-methods approach, combining surveys, interviews, laboratory analysis, and case studies to comprehensively examine the current state of food processing practices, evaluate innovative technologies, assess their impact, and provide recommendations for improvement. The findings reveal the persistence of traditional processing practices, infrastructure challenges, and a digital divide between urban and rural areas. However, promising innovations in advanced machinery, preservation techniques, biotechnology, food safety technologies, and sustainability initiatives are emerging. These innovations enhance food quality, safety, and availability. Recommendations include promoting technology access, infrastructure development, knowledge transfer, and policy support. By addressing these challenges and embracing technology-driven solutions, West Java Province can transition toward a more efficient, safe, and sustainable food processing sector, benefiting both the industry and consumers.